'Deregisterment' and 'fossil forms': the cases of gan and mun in 'Yorkshire' dialect: The changes in what features constitute 'Yorkshire' dialect from the 19th century to the 21st. Issue 1 (28th November 2016) - Cooper, Paul
Abstract : Recent work in sociolinguistics has illustrated that language features can become explicitly linked with numerous and multiple social values for certain speakers 1 . These language features can include pronunciations, words, or phrases, and the kind of associated social values can include social class or geographical region, notions of aesthetics or correctness, or more abstract concepts like 'authenticity' or 'friendliness'. When speaker awareness leads to the linking of language features with social values in this way, the features may have undergone enregisterment, defined by Agha (2003: 231) as 'processes through which a linguistic repertoire becomes differentiable within a language as a socially recognized register of forms'. I will focus here on the explicit association of a geographical location, Yorkshire 2, with a distinct set of language features.